Goldilocks and the three bears - Schmidt, Karen (Reading, Mass. Addison-Wesley, 1989)
A tired and hungry little girl finds the house of the three bears where she helps herself to food and goes to sleep.
Keywords: Folklore; Bears -- Folklore